Copper catalyzed dearomatization by Michael-type addition of indolyl ynones: divergent synthesis of functionalized spiroindoles and cyclopenta[c]quinolin-3-ones. Issue 10 (4th April 2022) - Ru, Guang-Xin; Zhang, Meng; Zhang, Ting-Ting; Jiang, Xiao-Lei; Gao, Guang-Qin; Zhu, Xiu-Hong; Wang, Shun; Fan, Cai-Ling; Li, Xiao; Shen, Wen-Bo
Abstract : Described herein is a copper-catalyzed multifunctionalization of indolyl ynones, allowing the synthesis of dihalogen-substituted spiroindoles. This Cu catalysis is also applicable to the synthesis of cyclopenta[ c ]quinolin-3-ones via decarbonylation. Abstract : Described herein is a novel copper-catalyzed multifunctionalization of alkyne-tethered indoles, allowing the practical and efficient synthesis of a diverse array of valuable dihalogen-substituted spiroindoles containing tetrasubstituted alkenes which can be readily functionalized further to obtain various spiroindolines. The construction of synthetically challenging quaternary spirocyclic carbons and tetrasubstituted alkenes is easily achieved in a single operation. Importantly, an unexpected dearomatization of alkyne-tethered indoles via Michael-type addition is involved in this tandem sequence. Furthermore, this Cu catalysis is also applicable to the regioselective synthesis of cyclopenta[ c ]quinolin-3-ones from readily available indolyl ynone homologues by skeletal rearrangement.